2019
DOI: 10.2215/cjn.11590918
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Over Time of Volume Status and PD-Related Practice Patterns in an Incident Peritoneal Dialysis Cohort

Abstract: Background and objectivesVolume overload is frequent in prevalent patients on kidney replacement therapies and is associated with outcome. This study was devised to follow-up volume status of an incident population on peritoneal dialysis (PD) and to relate this to patient-relevant outcomes.Design, setting, participants, & measurementsThis prospective cohort study was implemented in 135 study centers from 28 countries. Incident participants on PD were enrolled just before the actual PD treatment was started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 28 publications
6
75
1
1
Order By: Relevance
“…Specifically, extracellular volume control did not vary with time once accounting for potential confounders. An earlier large study of incident PD patients also reported stable extracellular volume status over time 27 . We also tested the effect of numerous variables on the evolution of extracellular volume status over time, but were unable to demonstrate any demographic or other factor having any effect.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, extracellular volume control did not vary with time once accounting for potential confounders. An earlier large study of incident PD patients also reported stable extracellular volume status over time 27 . We also tested the effect of numerous variables on the evolution of extracellular volume status over time, but were unable to demonstrate any demographic or other factor having any effect.…”
Section: Discussionmentioning
confidence: 95%
“…Fluid overload is common in PD patients [37][38][39][40][41][42][43][44] and an independent predictor of all-cause mortality [39,42]. Ng et al [41] reported that fluid overload was common in asymptomatic incident PD patients and a strong predictor of patient survival and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that the majority (56.4%) of patients were moderately and severely overhydrated based on a cutoff level of >1.1 L. At initiation of PD, the mean OH volume was 1.9 ± 2.4 L; however, 1 year later, OH had decreased at 1.2 ± 1.8 L and remained relatively stable between the 2nd and 3rd year of follow-up (1.4 ± 1.8 L and 1.4 ± 1.7 L, respectively). According to a linear-mixed model analysis, age, male gender, and presence of diabetes were associated with fluid overload at 1st month (adjusted difference in relative OH at 1st month for age: 0.1, 95% CI 0.0–0.1 per 1 year of increase; for male gender: 3.4, 95% CI 2.1–4.7; for presence of diabetes: 4.8, 95% CI 3.3–6.2) [70]. Of note, BIA techniques showed that PD patients presented with higher ECW content compared with HD patients, while studies with serum biomarkers indicated no differences in their levels between PD and HD [9, 71].…”
Section: Bia Techniquesmentioning
confidence: 99%